Vaccination services—not populations—are ‘hard-to-reach’: what can health authorities in Africa do to improve access? - Abdu A. Adamu; Chukwudi A. Nnaji; Charles S. Wiysonge (Discover Public Health)
Abstract Immunization coverage inequity is a serious problem in many African countries, and this has implications for the persistent spread of vaccine-preventable diseases. “Hard-to-reach populations” is widely used to describe communities that are difficult to reach with vaccination services on account of geographic, social, or economic circumstances. However, insights from existing studies on factors that affect access to vaccination services in African contexts highlight a preponderance of supply-side problems compared to demand-side issues. This suggests that suboptimal vaccination coverage in these settings has more to do with vaccination services being “hard to deliver” than populations being hard to reach. Therefore, there is a need to use “hard-to-reach population” in reference to immunization with caution. This perspective article advocates for policy-makers and health authorities in Africa to re-evaluate why they struggle to achieve optimal vaccination coverage across diverse settings and reimagine current vaccination service delivery models through an equity lens. Some suggested areas of focus are also outlined.